Treatment of iron deficiency in patients after acute decompensation: a new target in the treatment of heart failure - I. V. Zhirov; N. V. Safronova; S. N. Tereshchenko (Российский кардиологический журнал, 2022)
Iron deficiency  (ID) is one of the most common  comorbidities  in patients with heart failure (HF). ID is a strong independent predictor of outcomes  in HF patients. ID reduces  quality of life, exercise  tolerance,  and survival in patients with HF, regardless of anemia status. The latest 2021 guidelines recommend  initiating ID treatment at a ferritin <100 µg/L, or 100 to 299 µg/L, when transferrin saturation is less than 20%. The FAIR-HF and CONFIRM-HF studies have shown improvements in symptoms,  quality of life, and functional status in patients with stable HF and ID after intravenous administration of ferric carboxymaltose (FCM). Moreover, the results of these studies showed a reduced  risk of hospitalization for HF, which was later confirmed  in a subsequent  meta-analysis. Finally, the AFFIRM-AHF study, which evaluated the effect of FCM administration on outcomes  in patients hospitalized for acute HF/acute decompensated  HF, found a significant reduction in HF-related readmissions among patients treated with FCM.